Live-virus neutralization of the omicron variant in children and adults 14 months after SARS-CoV-2 wild-type infection - Stich, Maximilian; Benning, Louise; Speer, Claudius; Garbade, Sven; Bartenschlager, Marie; Kim, Heeyoung; Jeltsch, Kathrin; Tabatabai, Julia; Niesert, Moritz; Janda, Aleš; Renk, Hanna; Elling, Roland; et al. (Journal of medical virology, 2023)
Data on cross-neutralization of the SARS-CoV-2 omicron variant more than 1 year after SARS-CoV-2 infection are urgently needed, especially in children, to predict the likelihood of reinfection and to guide vaccination strategies. In a prospective observational cohort study, we evaluated live-virus neutralization of the SARS-CoV-2 omicron (BA.1) variant in children compared with adults 14 months after mild or asymptomatic wild-type SARS-CoV-2 infection. We also evaluated immunity to reinfection conferred by previous infection plus COVID-19 mRNA vaccination. We studied 36 adults and 34 children 14 months after acute SARS-CoV-2 infection. While 94% of unvaccinated adults (16/17) and children (32/34) neutralized the delta (B.1.617.2) variant, only 1/17 (5.9%) unvaccinated adults, 0/16 (0%) adolescents and 5/18 (27.8%) children <12 years of age had neutralizing activity against omicron (BA.1). In convalescent adults, one or two doses of mRNA vaccine increased delta and omicron neutralization 32-fold, similar to a third mRNA vaccination in uninfected adults. Neutralization of omicron was 8-fold lower than that of delta in both groups. In conclusion, our data indicate that humoral immunity induced by previous SARS-CoV-2 wild-type infection more than 1 year ago is insufficient to neutralize the current immune escape omicron variant.
Gesehen am 22.05.2023